Memory and Reality: Exploring Magical Realism in Susan Abulhawa’s 'Against The Loveless World - Mahnoor Shahid Mufti; Zarmeena Khan (University of Chitral Journal of Linguistics and Literature, 2024)
This research aims to critically scrutinize the current Genocidal Movement against Palestinian Muslims and make an analysis of the sufferings of people who have witnessed war and its trauma through the character of Nahr in Susan Abulhawa’s novel Against The Loveless World: A Novel. The work would be analyzed through the concept of Magical Realism from Postmodernist Literary Theory through Lois Parkinson Zamora and Wendy B. Faris’s book Magical Realism; Theory, History, community. Under this term, it is believed that the line between past and present is blurred in such a way that it highlights the elements of political and personal wars protagonists have witnessed by enfolding and unfolding a memory. The following theory uncovers the traumatic experiences of Bilal and Nahr in the colonizing state of Israel through their memories. This research is based on the enfolding and unfolding of memory and the blurring transition between them, and consideration would be on the aspects of political and personal wars of the protagonists under the theory of Magical Realism. This research analyzes the role of magical Realism in memory and how, through the constant shift between past and present, the traumatic experience of war against Palestinians is being highlighted.